PENGARUH LATIHAN DOUBLE LEG CONE HOP DAN LUNGES TERHADAP KEKUATAN TENDANGAN LONG PASS PEMAIN SSB INTERNAL FC U-19 - Septianingrum, Kartika; Kuncoro; Priagung; HS Muhammad; Mohammad (JOURNAL RESPECS (Research Physical Education and Sports), 2022)
This study aims to determine the effect of the practice of duoble leg cone hops and lunges on the level of long pass ability of SSB Internal FC soccer players, Ngawi. This study uses an experimental method with a "three groups pre-test-post-test design" design. The population in this study were football players from SSB Internal FC, Ngawi, which amounted to 30 people. Data analysis used t-test with a significance level of 5%. The results showed that (1) There was a significant effect of double leg cone hop exercise on the level of long pass strength of SSB Internal FC soccer players, Ngawi, with t count -14.230 > t table 2.447, and a significance value of 0.000 < 0.05, and a percentage increase of 8.69%. (2) There is a significant effect of lunges training on the level of long pass strength of SSB Internal FC soccer players, Ngawi, with t count -5,161 > t table 2.447, and a significance value of 0.001 < 0.05, and a percentage increase of 5.94 %. (3) The duoble leg cone hop exercise was better than the lunges exercise on the strength level of the SSB Internal fc soccer player, Ngawi, with t count 2.753 > t table = 2.365 and sig, 0.022 < 0.05.